2011
DOI: 10.1093/cvr/cvr202
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1-mediated up-regulation of cardiotrophin-1 is involved in the survival response of cardiomyocytes to hypoxia

Abstract: Hypoxia increased CT-1 levels in cardiac cells (in vitro and in vivo) through a direct regulation of CTF1 promoter by HIF-1α. This CT-1 activation by hypoxia may protect cells from apoptosis, thus supporting a protective role for CT-1 as a survival factor for cardiomyocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 41 publications
1
23
0
2
Order By: Relevance
“…Ultrasound in combination with CMBs and shPHD2 yielded the strongest gene down-regulation, consistent with previous reports 5, 51. HIF-1 activates the transcription of genes whose protein products may inhibit apoptosis in response to hypoxia/ischemia, including EPO, Cardiotrophin-1 (CT-1) and VEGF 52, 53, 54. We believe that silencing PHD2 is able to inhibit cell apoptosis under OGD.…”
Section: Discussionsupporting
confidence: 90%
“…Ultrasound in combination with CMBs and shPHD2 yielded the strongest gene down-regulation, consistent with previous reports 5, 51. HIF-1 activates the transcription of genes whose protein products may inhibit apoptosis in response to hypoxia/ischemia, including EPO, Cardiotrophin-1 (CT-1) and VEGF 52, 53, 54. We believe that silencing PHD2 is able to inhibit cell apoptosis under OGD.…”
Section: Discussionsupporting
confidence: 90%
“…In the ES cell system CT-1 exerts its pro-cardiogenic effect not through induction of cell hypertrophy but presumably by stimulation of cardiac cell commitment in early and proliferation in later stages of differentiation [42]. Further data of ours and others demonstrated that the expression of CT-1 is increased under hypoxia [1,38], which occurs under conditions of cardiac infarction, when cardiac cells become necrotic and cardiac regeneration is required. In this respect it has been previously reported that elevated levels of CT-1 occur in patients with unstable angina [46], acute myocardial infarction [19,48] and heart failure [47].…”
Section: Introductionmentioning
confidence: 58%
“…CT-1 expression has been shown to be regulated by various transcription factors that are activated only under pathophysiological conditions, such as hypoxia [29, 30]. Both systemic and local levels of CT-1 might be increased as a result of not only an upregulated production, but also a potential reduction in its degradation.…”
Section: Potential Sources Of Cardiotrophin-1mentioning
confidence: 99%